Electron choreography at the attosecond time scale. (1st February 2021) - Unzicker, B; Vaughan, J; Burrows, S; Tatum, B; Arthur, D; Olsson, T; Jain, S; Hart, T; Stringer, P; Laurent, G M
Abstract: In this work, we report on coherent control of electron dynamics in atoms via attosecond pulse-shaping. We show that the photoelectron emission from argon gas produced by absorption of an attosecond pulse train (APT) made of odd and even harmonics can be manipulated along the direction of polarization of the light by tuning the spectral components (amplitude and phase) of the pulse. In addition, we show that APTs produced with a two-color (400- plus 800 nm) femtosecond driving field exhibit high temporal tunability, which is optimized for an intensity ratio between the two colors in the range of 0.1 to 5%.